Living Together in Harmony: A Litera-Gramatics Perspective for Building Nationality in Indonesia based on Psalm 133:1-3 - Putrawan, Bobby Kurnia (Moriah Theological Seminary, 2024)
The background of this article focuses on Indonesia's challenges in building a strong nationhood amidst its ethnic, religious and cultural diversity. Psalm 133:1-3, which teaches the importance of living together in harmony and peace, offers relevant insights for nurturing unity in Indonesia. The purpose of this article is to explore the relevance of Psalm 133:1-3 in the context of Indonesian nationhood and how a lithic-grammatical perspective can be used to build a harmonious society. The method used is a literary-grammatical approach to analyze the text of Psalm 133:1-3, paying attention to the structure of the Hebrew language and its implications in social and national life. The results found show that the principle of living together in peace taught in the Psalms can be applied in the Indonesian national context, reminding the importance of appreciating diversity and maintaining unity. The contribution of this article is to provide a new perspective in understanding the biblical text as a moral source for building a strong, peaceful and sustainable nationhood in Indonesia, as well as exploring the potential of the biblical message in nurturing diversity in society.